Ngafe Culture: Friendship Communication Style among Gen Z Teenagers in the Perspective of Family Education - Sri Wahyuni; Ica Purnamasari; Kukuh Miroso Raharjo; M Haidar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
Ngafe culture has become an integral part of the friendship communication style among Generation Z teenagers. This phenomenon attracts attention, especially in the context of family education, as it relates to social dynamics and the role of families in guiding their children's social behaviour. This study aims to identify the different activities carried out by Gen Z teenagers in cafes and to understand the meaning of ngafe in the context of friendship communication from a family education perspective. This research uses a qualitative approach with a case study method where data is collected through observation, in-depth interviews and documentation. The research subjects were students in the city of Malang who were involved in café activities. The results showed that cafe activities are diverse, namely academic, social and networking, entertainment, and personal existential activities. Ngafe is important to Gen Z as a means of strengthening friendships, expressing self-identity and expanding social networks. Families play an important role in providing guidance and supervision to ensure that these activities are balanced and do not interfere with core responsibilities. The family's role in instilling social and ethical values is crucial in helping Gen Z to enjoy the ngafe culture in a positive and productive way.